Impact of Climate Change on the Cryosphere of the Ugam Chatkal National Park, Bostonliq District, Uzbekistan, During the Post-Soviet Period, Based on Remote Sensing and Statistical Analysis - Bokhir Alikhanov; Bakhtiyor Pulatov; Luqmon Samiev (Forum Geografi)
The cryosphere, including glaciers, snow cover, and ice sheets, plays a crucial role in global climate regulation. Therefore, monitoring is crucial for understanding climate dynamics at both regional and global scales. According to scientists studying global climate change, Central Asia is vulnerable to global temperature increases. However, research aimed at analyzing the impact of climate change on the regional cryosphere is lacking. This study investigated the impact of climate change on the cryosphere of the Ugam Chatkal National Park in Uzbekistan's Bostonliq District, focusing on the period following the dissolution of the Soviet Union (1991–2022). This study used remote sensing data and statistical analyses, such as the Mann–Kendall test and Sen's slope calculations, to evaluate trends in snow and ice cover, glacier extent, and vegetation health. Key indices, such as normalized difference vegetation index, normalized difference snow index, normalized difference glacier index, and normalized difference snow-ice index, were used to measure the mean values of these environmental parameters. The findings indicate a significant decrease in snow/ice cover (slope =-0.0048, tau =-0.193), underscoring the profound effects of climate warming on the region's water resources and ecological balance. The analysis highlights the urgency of implementing adaptive management strategies to mitigate these impacts, ensure the sustainability of water supply, and preserve biodiversity in Central Asia's vulnerable mountain ecosystems.